Auditory training can improve working memory, attention, and communication in adverse conditions for adults with hearing loss - Ferguson, Melanie A.; Henshaw, Helen (Frontiers Media, 2015)
Auditory training (AT) helps compensate for degradation in the auditory signal. A series of three high-quality training studies are discussed, which include, (i) a randomized controlled trial (RCT) of phoneme discrimination in quiet that trained adults with mild hearing loss (n = 44), (ii) a repeated measures study that trained phoneme discrimination in noise in hearing aid (HA) users (n = 30), and (iii) a double-blind RCT that directly trained working memory (WM) in HA users (n = 57). AT resulted in generalized improvements in measures of self-reported hearing, competing speech, and complex cognitive tasks that all index executive functions. This suggests that for AT related benefits, the development of complex cognitive skills may be more important than the refinement of sensory processing. Furthermore, outcome measures should be sensitive to the functional benefits of AT. For WM training, lack of far-transfer to untrained outcomes suggests no generalized benefits to real-world listening abilities. We propose that combined auditory-cognitive training approaches, where cognitive enhancement is embedded within auditory tasks, are most likely to offer generalized benefits to the real-world listening abilities of adults with hearing loss.